استخدام مخلفات عصر الزِّيتون في الحصول على منتجات صديقة للبيئة - حسين ندى أحمد (Latakia University Journal -Biological Sciences Series, 2015)
أجري البحث في محافظة طرطوس، في المنطقة الصّناعية وكلية الهندسة التقنية عام 2012، وأثبت البحث إمكانية الإسراع في التّخلّص من العرجوم من أمام المعصرة، وإمكانية تصنيع العرجوم من خلال كبسه وإنتاج قطع من العرجوم المكبوس للتدفئة المنزلية أو تحويله إلى فحم للشوي، وهذه منتجات قليلة الدخان، وذات رائحة خفيفة صديقة للبيئة، وأظهرت نتائج البحث الآتي: 1- إنتاج قطع من العرجوم المكبوس تستخدم للتدفئة يمكن التحكم بطول هذه القطع وبضغطها حسب الطلب، وبذلك نسهم في حلِّ مشكلة التدفئة في الشتاء، ونقلل من الأخطار البيئية لتراكم العرجوم. 2- لدى مقارنة السّماد العضوي Compost (الكومبوست) من العرجوم المسحوب الزِّيت مع سماد مخلوط قلف السنديان والقش وزرق الدجاج تبين وجود فروق معنوية لكل من الآزوت والبوتاس، وعدم وجود فروق معنوية لكل من المادة العضوية والرماد والفوسفور ودرجة الحموضة، وامتاز الكومبوست بمحتواه القليل من البولي فينولات، وبلغ رقم شتيازني في مستخلص كلٍّ من الماء البارد والساخن 0.277 و 8.62 على التوالي، في حين بلغ رقم شتيازني لسماد المخلوط في مستخلص الماء البارد والساخن 10 و 16 على التوالي. 3- عدم وجود فروق معنوية بين متوسطات كلٍّ من الحرارة النوعية وحرارة الاحتراق لكل من الفحم المنتج من الدّقة وفحم السنديان، وكان أقل فرق معنوي لهما 0.430 و 1.054 على التوالي، وامتاز فحم الدّقة برائحة شبه معدومة وبدخان قليل، وباشتعال سريع، وبلغت تكلفة إنتاج الكغ الواحد منه 5 ليرات سورية. The research had performed in Tartous county at Alsinaea area and Faculty of Technical Engineering in year 2012 .This investigation had confirmed the possibility of quick dispose of byrene and the possibility of byrene manufacture through byrene press and producing pieces for heating or producing barbecue charcoal. This products are with little smoke, smell and environment friendly. The results showed the following: 1- Producing pieces of byrene for heating with the possibility of controlling the strength and the press of pieces. With this we can contribule to environment protection and loosen the problem of heating in winter. 2- The comparison of organic fertilizer (Compost) from Byrene with mixture fertilizer from oak, straw and cock waste showed moral differences for nitrogen and kalium and no moral differences for organic substance, ashes, phosphourus and PH. The compost contains a little of Poly Phenolic. The SHETIANZY number for compost was with cold and hot water 0.277, 8.22, respectively and for mixture fertilizer 10, 16. 3- It was no moral differences between the specific heat and heat of combustion. The less moral difference was for both 0.430, 1.054, respectively. The barbecue charcoal from Dakka was with little smoke, smell and quick combustion. The producing cost of 1 kg was 5 syrian pounds.